Effect of Bypass Fat and Minerals Supplementation during Transitional Period on Plasma Levels of Thyroid Hormones, Metabolites and Postpartum Fertility in Crossbred Cows - Theodore, V.K.; Panchal, M.T.; Dhami, A.J.; Parmar, S.C.; Bhanderi, B.B.; Chaudhary , Sandhya (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
Twenty healthy advanced pregnant crossbred (HF x K) cows of 2-4 parity were included in the study from 2 weeks prepartum to 8 weeks postpartum. They were equally divided in to control (routine farm feeding-RFF) and treatment (RFF plus area specific multi-minerals @ 50 g/h/d and bypass fat @ 100-200 g/h/d) groups to evaluate the effect of bypass fat and minerals supplementation on plasma metabolites and hormonal profile and postpartum fertility. The plasma levels of T3 increased (P
Keywords: Crossbred cow; Transition period; Nutritional management; metabolic profile; postpartum fertility